Development of dense hydroxyapatite nanoceramic by pressureless sintering - Sittiporn Punyanitya (2018)
In order to improve fracture toughness, nanocrystalline hydroxyapatite (HA) powder was used for fabricate dense HA nanoceramic. The nanocrystalline HA powder was obtained with ball milling for 12 h from calcined natural bovine bone. The green compacts of HA nanopowder were sintered by pressureless sintering with non-linear heating rate sintering at 1200°C for 3 h. Fracture toughness and hardness properties of HA nanoceramic have been assessed using indentation technique. The fracture toughness values of sintered nanosized-HA powder is 3.5±0.1 MPa.m 1/2 , which is within those of human cortical bone. The nanostructure with liquid phase sintering of sintered nanosized-HA powder contributed to the increase of fracture toughness. The toughening mechanisms of pull-out of nanocrystalline HA and grain boundary sliding have been observed. © (2013) Trans Tech Publications, Switzerland.